2010
DOI: 10.2353/jmoldx.2010.100008
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA Hotspot Mutation Scanning by a Novel and Highly Sensitive High-Resolution Small Amplicon Melting Analysis Method

Abstract: Somatic mutations in the PIK3CA gene have been discovered in many human cancers , and their presence correlates to therapy response. Three "hotspot" mutations within the PIK3CA gene are localized in exons 9 and 20. High-resolution melting analysis (HRMA) is a highly sensitive, robust, rapid, and cost-effective mutation analysis technique. We developed a novel methodology for the detection of hotspot mutations in exons 9 and 20 of the PIK3CA gene that is based on a combination of PCR and HRMA. The PIK3CA HRMA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…Especially, to get reliable information for the molecular characterization of CTCs, sensitivity, specificity, and robustness of the mutation detection systems used is extremely important. We have previously developed a highly sensitive method for PIK3CA mutations based on HRMA (41). Despite the fact that this method is much more sensitive (1%) than the traditional Sanger sequencing, when we applied it in our CTC samples, we failed to detect CTC mutations as we initially expected.…”
Section: Survival Functionsmentioning
confidence: 70%
“…Especially, to get reliable information for the molecular characterization of CTCs, sensitivity, specificity, and robustness of the mutation detection systems used is extremely important. We have previously developed a highly sensitive method for PIK3CA mutations based on HRMA (41). Despite the fact that this method is much more sensitive (1%) than the traditional Sanger sequencing, when we applied it in our CTC samples, we failed to detect CTC mutations as we initially expected.…”
Section: Survival Functionsmentioning
confidence: 70%
“…14,31,32,[44][45][46] However, our group previously identified PIK3CA or AKT1 mutations in 65% of benign or atypical breast papillary lesions, 16 suggesting that a variety of proliferative lesions of the breast may harbor a high frequency of PIK3CA pathway mutations. In contrast, Li et al 13 studied a spectrum of proliferative and atypical breast lesions and found relatively fewer mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The temperatures used for embedding in paraffin cause further molecular reactions, some irreversible. [23][24][25][26][27][28] Artifacts could be the consequence of formalin damaging or cross-linking cytosine nucleotides. Thus, the Taq DNA polymerase would not recognize them and incorporate an adenosine instead of a guanosine (because of the socalled A-rule).…”
Section: Discussionmentioning
confidence: 99%